Islamic Law's Acceptance of LGBTQ Issues Based on the Maqasid al-Shariah Perspective - Eliza, Yunita; Arini, Rani Eka; Supriandi, Supriandi (West Science Islamic Studies, 2025)
This study examines the acceptance of LGBTQ issues within Islamic law through the perspective of Maqasid al-Shariah using a literature review of ten scholarly documents sourced from Google Scholar. The research explores how traditional juristic interpretations and contemporary reformist perspectives engage with sexual and gender diversity in light of the higher objectives of Shariah, namely the protection of religion (hifz al-din), life (hifz al-nafs), intellect (hifz al-‘aql), lineage (hifz al-nasl), and property (hifz al-mal). Findings indicate that classical jurisprudence predominantly views LGBTQ behaviors as incompatible with moral and social order, while modern scholarship advocates contextual, compassionate, and ethically principled approaches. The Maqasid al-Shariah framework provides a pathway for balancing adherence to divine objectives with the promotion of justice, human dignity, and social welfare. The study highlights that, although traditional positions remain restrictive, Islamic law has the potential to engage inclusively with contemporary social realities without compromising its ethical and spiritual foundations.